2020
DOI: 10.1093/mnras/staa259
|View full text |Cite
|
Sign up to set email alerts
|

What drives the redshift evolution of strong emission line ratios?

Abstract: We study the physical mechanisms that cause the offset between low-redshift and highredshift galaxies on the [O iii]λ5007/Hβ versus [N ii]λ6584/Hα "Baldwin, Phillips & Terlevich" (BPT) diagram using a sample of local analogues of high-redshift galaxies. These high-redshift analogue galaxies are selected from the Sloan Digital Sky Survey. Located in the same region on the BPT diagram as the ultra-violet selected galaxies at z ∼ 2, these high-redshift analogue galaxies provide an ideal local benchmark to study t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 56 publications
(86 reference statements)
5
27
0
Order By: Relevance
“…Steidel et al (2014) also argued that the line ratios found in high redshift galaxies were characteristic of harder ionising radiation fields, similar to those in stellar population models that include the effects of binary stars (Stanway et al 2014;Xiao et al 2018) or stellar rotation, which can affect the number and type of Wolf-Rayet stars produced, which in turn changes the hardness of the ionising spectrum (Conroy 2013) 1 . Bian et al (2020) reached a similar conclusion based on their analysis of the local counterparts of high redshift galaxies.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Steidel et al (2014) also argued that the line ratios found in high redshift galaxies were characteristic of harder ionising radiation fields, similar to those in stellar population models that include the effects of binary stars (Stanway et al 2014;Xiao et al 2018) or stellar rotation, which can affect the number and type of Wolf-Rayet stars produced, which in turn changes the hardness of the ionising spectrum (Conroy 2013) 1 . Bian et al (2020) reached a similar conclusion based on their analysis of the local counterparts of high redshift galaxies.…”
Section: Introductionsupporting
confidence: 56%
“…However, star formation rate is a confounding variable and when samples are compared at the same star formation rate they are found to have the same electron density (see also Liu et al 2008;Kaasinen et al 2018). Several studies have argued that simply selecting the extreme tail of the local star-forming galaxy population is insufficient to explain the evolution of the BPT diagram and that there are other differences that drive this behaviour (Steidel et al 2014;Bian et al 2020). It would be instructive to repeat the analysis carried out by Kashino & Inoue (2019) for the samples of high redshift galaxies used to establish the evolution in the BPT diagram, to see if the connection between HII region properties and galaxy properties evolves in a way not described by the 𝑧 = 0 relations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Steidel et al (2014Steidel et al ( , 2016 applied harder radiation fields using the binary Population and Spectral Synthesis code (BPASS) and these authors were able to produce models covering larger values of log([OIII]λ5007/Hβ), but always below the Kauffmann et al (2003) line. Other authors point to a higher ionization parameter or electron density as the main parameter producing the offset (e.g., Brinchmann et al 2008;Dopita et al 2016;Kojima et al 2017;Bian et al 2020). Nevertheless, current stellar synthesis models are unable to produce such hard radiation fields (Levesque et al 2010).…”
Section: Baldwin-phillips-terlevich and [Sii]λλ71731 Excitation Diagramsmentioning
confidence: 99%
“…Indeed, Steidel et al (2014Steidel et al ( , 2016 applied harder radiation fields using the binary Population and Spectral Synthesis code (BPASS) and these authors were able to produce models covering larger values of log([OIII]λ5007/Hβ), but always below the Kauffmann et al (2003) line. Other authors point to a higher ionization parameter or electron density as the main parameter producing the offset (e.g., Brinchmann et al 2008;Dopita et al 2016;Kojima et al 2017;Bian et al 2020). Nevertheless, current stellar synthesis models are unable to produce such hard radiation fields (Levesque et al 2010).…”
Section: Baldwin-phillips-terlevich and [Sii]λλ71731 Excitation Diagramsmentioning
confidence: 99%